Modeling business processes at industrial enterprises based on international approaches - A. A. Tikhomirov (Вестник университета)
Based on the author’s experience in applying project management methodologies at enterprises in various industries, a brief overview of current project management methodologies has been given in terms of historical background, as well as key concepts related to one or another of the most commonly used approaches. Attention has been paid to forming programs and project portfolios, and their unique distinguishing features have been briefly presented. As a current scientific publications analysis result, the key definitions of the enterprise architecture term have been given, as well as a brief overview of the most popular methodologies for designing enterprise architectures, including the main distinguishing features presentation. In the context of the project life cycle, a comparison with the two most popular enterprise architecture design methodologies has been given. Based on conceptually similar approaches in both project management methodology and enterprise architecture design, an architectural model of project, program, and portfolio management has been introduced (visualized). On the basis of the conducted research of modern methodologies of architectural design the stages of project (program, portfolio) architecture development and implementation have been proposed. The project (program, portfolio) architecture term interpretation has been formalized.